Analisis Kriminologi Terhadap Tindak Pidana Perdagangan Anak Di Bandar Lampung (Studi Kasus di Polda Lampung) - Satrio Nur Hadi; Dina Haryati Sukardi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Currently Child Trafficking in Bandar Lampung has become a problem that needs to be taken seriously, marked by the increasing number of cases that have arisen, particularly child trafficking through sexual exploitation, with a different modus operandi of crime. There are various forms of modus operandi that are used by actors in carrying out their actions, ranging from persuasion, fraud, or threats with violence. From this description, I am interested in researching about, What is the modus operandi of child trafficking in Bandar Lampung, how is the handling of child trafficking in Bandar Lampung? What are the barriers to handling child trafficking in Bandar Lampung? The research method used is normative legal research law that uses literature or empirical material that is sourced from interviews with several sources. The results showed that the form of modus operandi for cases of trafficking in persons / children in Bandar Lampung, namely Fraud by Fraud Employees Against Child Labor, Child Labor Similar to Modern Slavery, Prostitution Crimes through Social Media, Child Trafficking through Illegal Adoption, Kidnapping of Children Suspected By Organ Trafficking Syndicate. Furthermore, the number of cases in the city of Bandar Lampung increased in number from year to year, therefore the need for response to these cases. Crime prevention consists of three main parts, namely Pre-Emictive, Non-Penal Efforts that are Preventive, Penal Efforts that are Repressive. Then the Barriers to the Elimination of the Criminal Act of Child Trafficking in the City of Bandar Lampung, namely the legal substance aspects, legal structure aspects.